Balkrishna Doshi’s Contribution to the Development of Contemporary Architecture in India - Nasution, Diandra Fakhira; Rahman, Muhammad Fathur (Jurnal Koridor, 2023)
Balkrishna Doshi has more than 70 years as an architect contributing to hundreds of projects with the architectural firm he founded, VÄstu ShilpÄ Consultants, ranging from institutes, residences, art galleries, public spaces, and more. Doshi has also played a leading role as an educator, particularly in India. He founded the VÄstu ShilpÄ Foundation for Studies and Research in Environmental Design and the School of Architecture and Planning in Ahmedabad. With an understanding and appreciation of deep traditions in Indian character and architecture that he understood from childhood, regardless of local prefabrication and crafts, and developing a vocabulary that is in harmony with the history, culture, local traditions, and changing times in contemporary vernacular architecture in his home country, India. Keywords: Balkrishna Doshi, Contemporary Vernacular Architecture, Low-Cost Housing, India.